Tren Pendekatan STREAM (Science, Technology, Religion, Engineering, Arts, Mathematics) Terintegrasi Halal Pada Pembelajaran Kimia - Sa'diah, Fitri Yati; Agustina, Tri Wahyu; Cahyanto, Tri (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the development and impact of project-based chemistry learning with the STREAM approach integrated with halal values through bibliometric analysis. The method used is bibliometric analysis based on metadata from Publish or Perish (PoP) mapped using VOSViewer. The database was collected using Google Scholar over the last ten years. The analysis results show that despite fluctuations in the number of publications, there is an increasing research trend on this topic, especially in recent years. Data visualization indicates several main clusters depicting the relationships between these concepts. In conclusion, integrating halal values in chemistry learning with the STREAM approach not only enhances students' motivation and engagement but also develops their critical and creative thinking skills, providing valuable guidance for educators in implementing this approach to create a more inclusive and relevant learning environment.